Sharia Courts in Colonial Tashkent: A Study of Qāḍī Records and Social Dynamics (1865-1917) - Uktambek Sultonov (QURU’: Journal of Family Law and Culture, 2025)
This article examines the qāḍī (Islamic judge) records in Tashkent during the Russian colonial period (1865–1917) as a vital source for understanding the social and legal history of Muslim communities in Central Asia. Following administrative reforms implemented by the colonial government, Islamic courts were required to systematically record judicial proceedings in two types of documents: akt daftar (transaction records) and ḥukm daftar (judgment records). This study employs a social-historical approach using document analysis, with primary data drawn from colonial archives containing qāḍī records. The researcher investigates the institutional structure of Islamic judiciary, documentation systems, legal language used, and transformations in Islamic legal practices under colonial influence. The findings reveal that despite experiencing administrative changes driven by colonial governance, the qāḍī records remained a significant reflection of the community’s social and economic life. These documents illustrate legal practices related to trade, rental agreements, inheritance, endowments (waqf), and labor contracts, while also showing the interaction between Islamic legal traditions and colonial regulation. Furthermore, the qāḍī records provide insight into colonial efforts to control local religious institutions and their role in society. Thus, the study of qāḍī records offers a significant contribution to the legal and social history of Muslim communities in colonial Central Asia.